(3GdCUhd GdYdejI hGdJhLgGJ GdeSJbHdjI deOjQ GdbQf GdMGOj hGdYTQjfs - (3YHO GdMejO YHO GdaJGM(B, (3GdeZQHjs ((3GdGScfOQjI(B:s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY,s, 2006)
(3jVe EOGQI GdCYeGd Hjf GdeaGgje hGdeOGQS GdacQjI, GdeOjQhf hYedjI GJNGP GdbQGQGJ hJcfhdhLjG GdeYdheGJ, hXGFa GdeOjQhf aj efXeGJ GdCYeGd, JMdjd GdYhGed GdHjFjI hOQGSI GdeSDhdjI GdGLJeGYjI ddefXeGJ(B.s
(3HjHdjhZQGajG(B: (3U(B.595s
Keywords: (3EOGQI GdCYeGds; (3GJNGP GdbQGQGJs; (3GdGOGQIs